’CraftEng’ és az angol nyelv oktatása - Vanderstein, Noémi (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
Recent years - especially from the time of joining to the European Union - in the edu-cational system of Hungary, teaching foreign languages has a very important role. Among foreign languages, English is at the top position. This fact is in close relation to the situa-tion of the diplomats’ official language since it is English, too. Teaching English as a For-eign Language for beginners is a crucial point in the different regions of our country. Kin-dergartens and schools - supported by the local government or the church, either being private - find out a number of modes to invite more and more children into their institu-tions. One of the ideas is teaching foreign languages for young learners as early as possi-ble. To motivate young students is essential in life-long-learning so it is important to find the best way of introducing foreign languages for children. For teaching English and for staying in the race of the educational market, ’CraftEng’ is a new product.